BUILDING UNDERSTANDING AND AWARENESS OF ENVIRONMENTAL POLLUTION THROUGH COMIC - Riandi Riandi; Dieni Asma Mardiyah; Wahyu Surakusumah (Jurnal Pengajaran MIPA, 2016)
Environmental problems such as widespread pollution are ongoing threats to the livelihood of the current and future generations. Engaging learning media such as comics can be used to instill the importance of understanding our role in solving environmental pollution problems. This paper reports the promising benefit of using comics in building junior high school students understanding and awareness of water, soil, dan air pollution. Comic is a visual medium, and whether students' specific learning styles play a role in learning results was also determined and discussed.